2017
DOI: 10.1111/jog.13432
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the paracrine activity of mesenchymal stem cells derived from human umbilical cord, amniotic membrane and adipose tissue

Abstract: AM-MSCs show similar IL production as AD-MSCs, while UC-MSCs have a significantly different profile, which suggests diverse biological potential of both cell types for immunomodulative and regenerative therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 43 publications
(97 reference statements)
3
57
1
Order By: Relevance
“…Nevertheless, it remains elusive whether the increased levels of MMPs are based on active SC secretion or generated by host cells stimulated by applied SCs. The former mechanism is supported by in vitro data, showing that SCs from different sources possess the capacity to release MMPs at high levels [374][375][376]. However, Mias et al indicated that MSCs modulate the phenotype of cardiac fibroblasts in vitro and promoted the secretion of MMPs [364].…”
Section: Cardiac Remodelingsupporting
confidence: 52%
“…Nevertheless, it remains elusive whether the increased levels of MMPs are based on active SC secretion or generated by host cells stimulated by applied SCs. The former mechanism is supported by in vitro data, showing that SCs from different sources possess the capacity to release MMPs at high levels [374][375][376]. However, Mias et al indicated that MSCs modulate the phenotype of cardiac fibroblasts in vitro and promoted the secretion of MMPs [364].…”
Section: Cardiac Remodelingsupporting
confidence: 52%
“…An unbiased stable isotope labeling by amino acid-(SILAC-) based quantitative proteomic approach in cell culture coupled to LC-MS and validated by functional assays revealed that the secretome of MSCs isolated from fetal skin is superior to that of adult skin [109]. When considered across different sources, different patterns emerge: the secretion of VEGF and TGF-β1 is higher and comparable in AM-MSCs and AT-MSCs, while CB-MSCs show lower production, with an associated opposite trend for HGF (higher secretion in CB-MSCs vs. AM-MSCs) [110,111]. On the other hand, Kim et al showed increased secretion of 5 Stem Cells International VEGF-A, HGF, bFGF, and ANG-1 from amniotic-derived MSCs when compared to AT-MSCs [112].…”
Section: Role Of Soluble Proteinsmentioning
confidence: 99%
“…Adding to that, ADSC might be auto-induced by Tumor Growth Factor-β (TGF-β), TLR2, TNF-αresulting in different inflammatory factors secretion panel as already reported [16,[47][48][49]. In serum-free conditions, ADSC also secreted IL-6, IL-10, and TGF-β [44]. Distinct inflammatory signaling pathways were thus activated impacting the immunosuppressive activity of ADSC.…”
Section: Resultsmentioning
confidence: 70%
“…IL-6 cytokine effects on innate and adaptive immunity have been investigated within their both pro-inflammatory and anti-inflammatory contexts, but mostly presented as a pro-inflammatory cytokine having the ability to dually enforce or suppress immune responses depending on conditions. This cytokine is largely secreted by fresh ADSC than IL-10 and TNF-α [15][16][17]44], however, these concentration levels were reported for fresh expanded ADSC and remained relatively lowers when compared to those of cryopreserved ADSC. Indeed, cryopreservation increased IL-6 and TLR2 at both mRNA and protein levels, especially after P2 expansion.…”
Section: Resultsmentioning
confidence: 83%